Dampak Peningkatan Transformation Leadership Khususnya Pada Peran Work Engagement Dalam Pengembangan Self Leadership Pada Karyawan Pt Inovasi Teknologi Kosmetika - Laksono, Ali Ridho; Agustina, Tri Siwi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to measure the influence of transformation leadership on work engagement through self-leadership. Quantitative research method using non-probability sampling and purposive sampling technique of 156 employees. Data analysis techniques using Smart PLS software with hypothesis testing using PLS-based SEM. The results of the research show that transformation leadership has an effect on work engagement through self-leadership in employees of PT Innovation Teknologi Kosmetika. The research conclusion is that the higher the level of transformational leadership carried out, the greater the work engagement and self-leadership